FIELD GEOLOGY OF GUBI AREA, NORTHEASTERN NIGERIA - Rufai, F.A; Halilu, M.; Ahmed, H.A; Bukar, M. (IJRDO-Journal of Applied Science, 2017)
Basement rocks of the Gubi area of Northeastern Nigeria were assessed and found to comprise ofPre-Cambrian basement rocks invaded by Pan-African granites generally referred to as the‘Older Granites’. The area was composed mainly of Migmatite gneiss, granite gneisses and calcalkalinegranites. The tectonic structures in the study area trend mostly NE – SW andsubordinately NW-SE and N-S conform with the regional deformational structures whichoccurred during the Pan African thermotectonic events in the Nigerian basement.